(untitled) (Research, Society and Development, 2021)
Describe and characterize the student population observed at a therapeutic group meeting, held by a public university in the state of Pará. This is a qualitative, exploratory and descriptive experience report, of a critical-reflective nature that encompasses the concepts matriculation in mental health, aiming to provide psychological support to the academic community. During the presentation of the “Acolhecido” project, at the beginning of the 2020 academic year, we sought to integrate complementary educational activities and conversation with academics from the nursing, physical education, physiotherapy and biological sciences courses. The Therapeutic Group grounded psychological suffering in a conversation circle, which served as a psychotherapeutic device in the prevention of psychological suffering, and consequently, in the best promotion of psychological well-being. The university student faces a variety of risk conditions for his mental health and well-being, as well as the results obtained in the application of the educational activity and methods, it was possible to identify and discuss the signs and symptoms indicating stress, anxiety, depression and burnout among students.